MORPHOMETRY AND GENITALIA OF DRONES OF APIS HONEY BEE SPECIES FROM INDIA - SHASHIDHAR VIRAKTAMATH, (The Bioscan, 2015)
Morphometry of drones of Apis cerana ( N - 158),A. dorsata (N - 35) and A. florea (N - 33) collected from seven states viz. Andhra Pradesh (AP), Assam (AS), Jammu & Kashmir (JK), Karnataka (KA), Kerala (KL), Maharashtra (MH) and Tamil Nadu (TN), was studied for 19 morphological and one genitalial parameters. The data were subjected to factor, principal component and canonical discriminant analysis. Apisc eranadrones from Assam were the largest with body length of 11.47 mm while drones from Tamil Nadu were the smallest with body length of 9.61 mm.However, A. dorsata drones from Kerala measured 15.95 mm in length as against the drones from Assam which measured only 12.45 mm. Drones of A. florea from Karnataka, Assam and Andhra Pradesh were larger with body length ranging from 11.04 to 11.36 mm while the drones from other states varied from 10.43 to 10.77 mm. Principal component and canonical discriminate analysis of morphometric data of A. cerana drones from seven states resulted in formation four clusters (drones from JK +AS; AS alone; JK + AS + KA; and AP + KA + KL + MH + TN). A. dorsata drones also formed four overlapping clusters (AS + KA + KL + MH; AS + KA + KL + MH + TN; KA alone and KA+ MH) while A. florea drones formed 5 clusters in factor analysis (drones from AS alone; KA + TN; AP + KA + MH + TN; AP + KA + TN and KL + TN) and 3 clusters in canonical discriminant analysis (Drones from AS alone; AP + KA + KL and MH + TN). Genitalia of A. cerana, A. dorsata and A. florea from India have been described and illustrated for the first time. It is concluded that the drones of A. cerana and A. dorsata from seven states formed overlapping clusters indicating extensive migration and interbreeding among the populations while A. florea drones of Assam are distinct from the southern states. The genitalia of drone of each species of honey bee are distinct but the genitalial structures within the species varied.